Faktor yang Memengaruhi Kesalahan Persepsi Ibu tentang Status Gizi Anak - Arfianti Arfianti; Tri Muhti Puja Kesuma; Muhammad Beni Septima; Riefni Silara Dini; Fifia Chandra (Faculty of Public Health, Hasanuddin University, Makassar, 2019)
Malnutrition is a significant health problem among Indonesian children. Mothers play a very importantrole in the prevention of childhood malnutrition. This study aimed to compare the child’s nutritional statusbased on mothers’ perception and anthropometry measurement and to analyze contributing factors of maternalmisclassification of a child’s weight status. This was an analytical observational study with a cross-sectional design.Research subjects included 250 mothers of grade 4 and 5 students from 6 elementary schools in Pekanbaru cityrecruited by the proportional quota sampling method. The Nutritional status of children was classified accordingto the 2006 World Health Organization (WHO) anthropometry standard. Mothers’ perception of child’s weightstatus was collected using questionnaires. Based on anthropometry measurement, 28% and 10% of children wereoverweight and underweight, respectively. In contrast, according to mothers, 4,8% of children were overweightand 12,8% ofchildren were underweight. As many as 34.8% of mothers had incorrect perceptions about thenutritional status of their children and there was a poor agreement of mothers’ perception and child’s nutritionalstatus (Kappa coefficient of 0,02). Working mothers were more likely to underestimate their child’s weight statuscompared to stay-at-home mothers (p=0,004).